IMPLEMENTASI KURIKULUM 2013 SAAT PEMBELAJARAN DARING DI MAN 2 MADIUN MELALUI TAHAPAN PERENCANAAN, PELAKSANAAN DAN EVALUASI - Anggi Puspitasari; Inani Mahmudah; Clariesa Alit Maharani; Intan Diyah Pratiwi; Darmadi Darmadi (LPPM Universitas Bina Bangsa, 2021)
Indonesia is a country that always tries to keep up with the developments of the Globalization Era and persuasion, every change of Head of State (President) as well as Change of Minister of Education, curriculum changes are made. The curriculum in Indonesia has undergone several changes until finally a new curriculum was born in 2013, which we usually call the 2013 Curriculum. The 2013 curriculum is running well in several schools. However, without being planned in early 2020 in various countries in the world experiencing the covid-19 pandemic, it has an impact on the learning of school students in Indonesia. What students usually do offline learning is now done boldly. In accordance with the problems that occurred, this study aims to analyze